RANCANG BANGUN LAMPU OPERASI LED MOBILE DIGITAL - M Yasir Pohan (Jurnal Bionatural, 2025)
Design of Mobile Digital LED Operating Lamp an operating lamp tool has been made which aims to determine the maximum power of the LED lighting used. This research was conducted using 15 led lamps and the data was obtained from measuring the light intensity value which has been set to the intensity level from 0-9 on the seven segment. Data was taken using a lux meter to show the results of lux measurements produced by operating lights with an average intensity measurement result of 97.2 lux for the lowest intensity level and 714.3 lux for the highest intensity level.